1986
DOI: 10.1002/star.19860381007
|View full text |Cite
|
Sign up to set email alerts
|

Tepary Bean Starch. Part II. Rheological Properties and Suitability for Use in Foods

Abstract: Rheological and organoleptic properties of starch from tepary bean (Phaseolus acutifolius var. latifolius) have been investigated. Gelatinization was determined to be a single‐step process. The pasting properties were similar to those reported for other legume starches. It was stable when cooked at 95°C for 15 min and showed a progressive increase in viscosity when cooled to 50°C. At 4 and 6% concentrations (w/w) tepary starch pastes exhibited a type C viscosity pattern whereas at concentrations of 7% and abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…Differences between the pasting properties of pea starch observed in the current study and values reported by others were attributed, in part, to differences in the analytical methodology employed (viscoamylograph with a starch slurry concentration of 90 g kg −1 w/v and pH 5.5 in Ratnayake et al 12 versus viscoamylograph with a starch slurry of 56 g kg −1 (w/v) in Davydova et al 32 versus RVA with a starch slurry concentration of 80 g kg −1 w/v and pH 7.0 in the current study) since increasing the starch concentration increases pasting temperature and the viscosities at 95 °C, after the 95 °C hold and at 50 °C 35. Variations in starch behaviour among pea genotypes, as observed in the current study and as described by Ratnayake et al 12 are relatively small compared, for example, to variations observed among 21 Australian wheat genotypes,5 where PV, To, Tp, Tc, and Δ H were 280–768 Brabender units, 46–53 °C, 57–62 °C, 64–78 °C and 4.6–13.8 J g −1 , respectively.…”
Section: Resultssupporting
confidence: 48%
“…Differences between the pasting properties of pea starch observed in the current study and values reported by others were attributed, in part, to differences in the analytical methodology employed (viscoamylograph with a starch slurry concentration of 90 g kg −1 w/v and pH 5.5 in Ratnayake et al 12 versus viscoamylograph with a starch slurry of 56 g kg −1 (w/v) in Davydova et al 32 versus RVA with a starch slurry concentration of 80 g kg −1 w/v and pH 7.0 in the current study) since increasing the starch concentration increases pasting temperature and the viscosities at 95 °C, after the 95 °C hold and at 50 °C 35. Variations in starch behaviour among pea genotypes, as observed in the current study and as described by Ratnayake et al 12 are relatively small compared, for example, to variations observed among 21 Australian wheat genotypes,5 where PV, To, Tp, Tc, and Δ H were 280–768 Brabender units, 46–53 °C, 57–62 °C, 64–78 °C and 4.6–13.8 J g −1 , respectively.…”
Section: Resultssupporting
confidence: 48%
“…4) was similar to that observed for the swelling power. In a similar way, the water solubility of baby lima bean starch is lower than the one reported by Abbas et al [36] for starches of winged bean (15.4%) and tepary bean (17.9%). This could be due to the fact that low molecular weight amylose can leave the swollen starch granules and dissolve in water.…”
Section: Functional Propertiessupporting
confidence: 63%
“…3) resembled that observed for swelling power in that solubility increased as temperature increased. Velvet bean solu- bility is also greater than those reported for winged bean (15.4%) and tepary bean (17.9%) starches [37]. The corn starch, in comparison, exhibited only a moderate increase in solubility as temperature increased, reaching 15.8% at 90 °C, less than the 16.2% reached by velvet bean starch at the same temperature.…”
Section: Swelling Behavior In Other Legumes Is Variable Swelling Simmentioning
confidence: 58%